Arquivos pessoais, arquivos de memória e o processo de indexação - Oliveira, Isabel Cristina Borges de (2009)
This dissertation seek to discuss the personal archives indexing by analyzing the personal archive of Ubaldino do Amaral Fontoura index. Besides, the archival theoretical questions like normalization, standardization and controlled vocabulary construction in order to improve the answer to the user. The research also examines personal archives as memory archives and how the access point definition interferes in the issue of environment and erasing the memory